Synthesis and characterization of ZnO thin film memristor - Mohd Yusoff, Marmeezee; Ani, Mohd Hanafi; -, Suryanto (Trans Tech Publications, Switzerland, 2013)
ZnO films were deposited on Cu substrate using electrodeposition and thermal oxidation method. The effect of deposited thin film thickness varied with deposition time was discussed. Synthesized ZnO films were characterized using XRD, FE-SEM and electrical measurement. The results from electrical measurement showed the deposited ZnO exhibits pinched hysteresis I–V curves. The synthesized ZnO shows a potential applications and options in production of a noncomplex and low cost memristor.